Control of intrinsic pacemaker frequency and velocity of colonic migrating motor complexes in mouse - Barnes, Kyra J.; Beckett, Elizabeth A.; Brookes, Simon J.; Sia, Tiong Cheng; Spencer, Nick J. (Frontiers in Neuroscience, 2014)
The mechanisms that control the frequency and propagation velocity of colonic migrating motor complexes (CMMCs) in mammals are poorly understood. Previous in vitro studies on whole mouse colon have shown that CMMCs occur frequently ( every 1-3 mins) when the colon is devoid of all fecal content. Consequently, these studies have concluded that the generation of CMMCs and the frequency which they occur does not require the presence of fecal content in the lumen. However, in these studies, stimuli have always been unavoidably applied to these empty colonic preparations, facilitating recordings of CMMC activity. We tested whether CMMCs still occur in empty whole colonic preparations, but when conventional recording methods are not used. To test this, we used video imaging, but did not utilize standard recording methods. In whole isolated colons containing multiple endogenous fecal pellets, CMMCs occurred frequently (2.2±0.1/min) and propagated at 2.16±0.2mm/sec. Surprisingly, when these preparations had expelled all content, CMMCs were absent in 11/24 preparations. In the remaining preparations, CMMCs occurred rarely (0.16±0.02/min) and at reduced velocities (0.75 ± 0.75 mm/sec), with reduced extent of propagation. When conventional recording techniques were then applied to these empty preparations, CMMC frequency significantly increased, as did the extent of propagation and velocity. We show that in contrast to popular belief, CMMCs either do not occur when the colon is free of luminal contents, or, they occur at significantly lower frequencies. We believe that previous in vitro studies on empty segments of whole mouse colon have consistently demonstrated CMMCs at high frequencies because conventional recording techniques stimulate the colon. This study shows that CMMCs are normally absent, or infrequent in an empty colon, but their frequency increases when fecal content is present, or, if in vitro techniques are used that stimulate the intestine.